2011
DOI: 10.1590/s0103-21002011000100008
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da prática da amamentação em grupo de mães adolescentes

Abstract: Objectives: To describe the breastfeeding experience among teenage mothers, to identify past breastfeeding experience, and to identify events / situations perceived as obstacles to their current breastfeeding. Methods: An exploratory study was conducted with 80 adolescent mothers in a low-risk maternity setting in Ribeirão Preto-SP. A structured data collection tool was administered three times (at hospital discharge, during consultation between 10-15 days postpartum, and by telephone one month after discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
23

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 11 publications
1
12
0
23
Order By: Relevance
“…The average age of adolescent mothers in this study was 17.5 years, characterizing as mothers who became pregnant not so early, so the risk factors are somewhat mitigated. Similar results were found by Camarotti et al 18 . Higher parental educational level has been positively associated with appropriate motor and cognitive 19,20 performance of children of different ages 19 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The average age of adolescent mothers in this study was 17.5 years, characterizing as mothers who became pregnant not so early, so the risk factors are somewhat mitigated. Similar results were found by Camarotti et al 18 . Higher parental educational level has been positively associated with appropriate motor and cognitive 19,20 performance of children of different ages 19 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have also reported the vulnerable socio-economic situation of families of adolescent mothers 18 ; and the lower the family income, the greater the vulnerability of the child development process 6 . However, in this study, the socioeconomic status did not impact the development of babies of adolescent mothers, since over time, babies of adolescent and adult mothers had similar motor and cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…This is a worrisome finding since authors showed that the interruption of exclusive breastfeeding through the introduction of cow's milk is most significant among low-income families [24]. There was predominance of primiparae mothers, which is also reasong for worrying bacause they are inexperient, with more doubts and difficulties in relation to breastfeeding, and may also suffer more easily negative influences on the act of breastfeeding [25]. On the other hand, if the adolescent is confident about breastfeeding and is well guided and assisted, especially at the beginning of this process, she will develop the necessary confidence to continue breastfeeding her baby.…”
Section: Discussionmentioning
confidence: 99%
“…Isto implica em respeitar as limitações e saberes prévios da adolescente e compartilhar das vivências de sua realidade (16). Isto implica na criação de estratégias que possibilite conhecê-las em seus projetos de vida, de maneira integrada com sua família e meio social, tornando-as protagonistas das vivências em amamentação, por meio da construção de vínculo e do acolhimento visando garantir uma atenção integral (17).…”
Section: Discussão E Conclusãounclassified